Dampak Buruk Dari Judi Online Terhadap Masyarakat Di Desa Rulung Sari Kabupaten Lampung Selatan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
When science and technology develop, there are new methods for committing crimes. One of the criminal acts is online gambling. This can happen because current media and facilities make it easier for people to access gambling sites and applications. To eliminate this act, a provision is needed that strictly prohibits this act and determines the consequences for those who violate it. Online gambling violates Indonesian law and societal values. The aim of this research is to observe the negative impact of online gambling on the community in Rulung Sari Village, South Lampung Regency. The research methodology used includes surveys, interviews and data analysis to understand the social, economic and psychological impacts caused by online gambling practices. Research shows that online gambling has had a significant negative impact on the social structure of society, harming the local economic sector, and causing psychological problems among individuals and families. The implications of these findings underscore the urgency of the need for preventive and intervention measures to reduce the negative impacts of online gambling and protect the welfare of the Rulung Sari Village community as a whole.